Government debt post COVID-19: Back to golden rules - Christian Breuer (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2021)
The COVID-19 crisis has caused public debt to increase dramatically, which is why the German and European fiscal rules are currently suspended. In addition to the new assessment of the fiscal costs at low interest rates, the discussion on the reintroduction of fiscal rules in Germany and Europe should take into account the function of government bonds as a safe asset and an instrument to combat the liquidity trap as well as the net return on productive government investments. For practical reasons, the return to the classic Golden Rule, which aims to limit net debt and promote government investment in the interest of future generations, is recommendable.
Keywords: E62; H56; H63; 330; Government Debt; Fiscal Rules; Low Interest Rates